Answer:
B) -1
The 'x' value =-1 and y =-7
The solution of the given system of equations
(-1,-7)
Step-by-step explanation:
<u><em>Step(i)</em></u>
Given that the system of equations
x-y = 6 ..(i)
y = 2x -5 ..(ii)
By using substitution method,
substitute y=2x-5 in equation (i) , we get
x -(2x-5) =6
x -2x+5 =6
-x = 6-5
-x =1
x=-1
<u><em>Step(ii):-</em></u>
Put x=-1 in equation (ii) , we get
y = 2(-1) -5 = -2-5 =-7
The solution of the given system of equations
(-1,-7)
I would say 0, -5/2 but I am unsure as I have this same problem
Answer:
Step-by-step explanation:
-0.8078217663
the missing number should be the square root of the last number times 2 for a perfect trinomial
so square root of 49 = 7
7*2 =14
so the missing number should be 14
This appears to be about rules of exponents as much as anything. The applicable "definitions, identities, and properties" are
i^0 = 1 . . . . . as is true for any non-zero value to the zero power
i^1 = i . . . . . . as is true for any value to the first power
i^2 = -1 . . . . . from the definition of i
i^3 = -i . . . . . = (i^2)·(i^1) = -1·i = -i
i^n = i^(n mod 4) . . . . . where "n mod 4" is the remainder after division by 4
1. = -3^4·i^(3·2+0+2·4) = -81·i^14 =
812. = i^((3-5)·2+0 = i^-4 =
13. = -2^2·i^(4+2+2+(-1+1+5)·3+0) = -4·i^23 =
4i4. = i^(3+(2+3+4+0+2+5)·2) = i^35 =
-i